Fast prototyping made by the technique of three-dimensional printing in surgery and implantology (Research, Society and Development, 2021)
Fast prototyping is a technology that has been widely used today in odontology as a way to facilitate the daily life of dentists that constitute an association of medical-dental imaging with the computer systems Computer Aided Design (CAD), this technique has the ability to acquire bio models compatible with human anatomy. This academic work aims to review the state of the art showing the benefits and advantages of fast prototyping models for planning and reduction of surgeries in implant dentistry and maxillofacial. Thus, a qualitative bibliographic research was used to study and draw up this work. In the first part, it was found that fast prototyping made by the three-dimensional impression technique is the most effective method, bringing an efficient result for the dental surgeon and the patient. In the second part of this work, several ways to provide and help the life of the dentist in implant dentistry and maxillofacial surgeries were analyzed, being beneficial in the patient's post-surgery with faster healing and the best final result. In the third part, it was found that the computer system is the software used to convert the data acquired in computed tomography.